Pneumonia, lymphocytes and C-reactive protein are valuable tests for predicting surgical intervention in necrotizing enterocolitis - Yu, Daiyue; Yang, Huirong; Zhong, Chen; Fan, Kaisi; Zeng, Guichang; Zhang, Mengzhen; Zhao, Qianyun; Yang, Jiaming; Yang, Liucheng; Wu, Kai (Frontiers in Pediatrics, 2023)
Background: Necrotizing enterocolitis (NEC) is one of the important causes of neonatal death, and proper timing of operation is of critical significance. This study aimed to explore the high-risk factors for NEC requiring surgical intervention and to provide a reference for its clinical diagnosis and treatment.Methods: Clinical and radiological evidence of NEC neonates admitted to Zhujiang Hospital of Southern Medical University and Zhongshan Boai Hospital from January 2010 to October 2022 were retrospectively analyzed. Patients were divided into surgical group and conservative group according to whether they underwent surgery or not. Univariate analysis of the clinical data of the two groups was conducted, and multivariate logistic regression analysis was then performed for statistically significant results in the univariate analysis.Results: 267 infants were included in this study, of which 90 patients underwent surgical intervention for NEC and 177 conservation treatment. The univariate analysis showed that the gestational age, pneumonia, leukocytes, lymphocytes, erythrocytes, platelets, C-reactive protein, and blood glucose were statistically significant in the surgical group compared to the conservative group (All P<0.05). Furthermore, the results of multivariate logistic regression analysis showed that compared to the conservative group, patients in the surgical group had a higher proportion of pneumonia (OR=2.186, CI: 1.076-4.440; P=0.030), lower lymphocyte values (OR=0.806, CI: 0.667-0.974; P=0.004), and higher C-reactive protein values (OR=1.009, CI: 1.003-1.016; P=0.026). This is a provisional file, not the final typeset article Conclusions: Pneumonia, decreased lymphocytes, and elevated C-reactive protein are potential highrisk factors for neonates with NEC requiring surgical intervention and may have potential clinical implications for predicting surgical risk.